Application of Guided Discovery Learning Model to Enhance Student Learning Interest and Results in Science Subjects Fifth Class SD Inpres Tompi Bugis District of South Kulawi - Asisa, Nur; Hamzah, Baharuddin; Mustapa, Kasmuddin (Universitas Tadulako, 2017)
The purpose of this study was to increase interest and science learning outcomes in fifth-grade students of SD Inpres Tompi Bugis, Kulawi Selatan District through the application of guided discovery learning models. The method used is a classroom action research method with two cycles. Each cycle consists of two meetings. The results showed that in the first cycle of the first meeting, the observation of student activity obtained a value of 68%, was in the sufficient category, the value of students 'classical absorption was 74%, the students' classical learning completeness was 50% and the student's interest in learning 60% was in the sufficient category. In the first cycle of the second meeting, the observation of student activity obtained a value of 79%, in the good category, the value of students' classical absorption of 80%, 75% of students' classical learning completeness, and 74% of students' interest in learning were in a good category. The research was continued in cycle II with the results showing that the second cycle of the first meeting, the observation of student activity obtained a value of 80%, was in a good category, the value of students 'classical absorption was 84%, the students' classical learning completeness was 90% and the student's learning interest 80% were in the well. In the second cycle of the second meeting, the observation of student activity obtained a value of 90%, was in the very good category, the value of students 'classical absorption was 89%, the students' classical learning completeness was 100% and the student's interest in learning 90% was in the very good category. Thus, it can be concluded that the application of the guided discovery learning model can increase the interest and learning outcomes of fifth-grade students of SD Inpres Tompi Bugis, Kulawi Selatan District.